Priznanje krivde - Šugman Stubbs, Katja (Podjetje in delo, 2015)
CPP-K amendment to the Slovenian Criminal Procedure Code pushed our criminal procedure even a step further to the adversarial model since it introduced the principle that the guilty plea of the defendant factually ends the procedure. With such a solution we are partly departing from the basic criminal procedure principle of the continental criminal procedures, namely the search for the truth. Court and prosecutorial statistic and reports from practice show that the new solution has more than found its place. The article focuses on the role of judiciary in assessing the confessions (guilty plea) and is stressing the strong legislative authorizations provided for Slovenian judiciary in the process of deciding whether a confession is reasonable, voluntary and complete. The author is also analysing the anomalies which are taking place at the court and stresses the importance of the complete and thorough judicial check of guilty pleas.
Keywords: dokazi; kazenski postopek; kazniva dejanja; krivda; sodišča; sodna praksa; storilci